Sem analysis of muslim investor behavior towards sharia stock investment decisions on bei west java region - Rozak, Abdul; Kurniawan, Heri; Bahri, Khoirun Nisa; Andini, Sari Syifa (Jurnal Ekonomi, 2024)
Sharia-based stock investment is a current trending topic that is very important to develop. This shows that Islam, as the majority religion in Indonesia, is very concerned about increasing the halalness of investment instruments, their benefits and benefits for the people. In the context of investment behavior in the capital market, investors' religious practices and activities (religiosity) are not entirely a reason for choosing sharia shares. This research aims to produce empirical evidence on sharia-based capital market investment research studies, especially for scientific development within the scope of the Muhammadiyah 'Aisyiyah College, which is viewed from the influence of accounting information quality factors, sharia principles and risk on sharia-based stock investment decision making through behavioral perceptions. individual as an intervening variable. This research is field research using a quantitative approach with respondents of 250 investors. The data analysis method uses path analysis and other programs that comply with applicable research method rules. The results of the research show that the variables of information quality, subjective norms, sharia principles and risk have a significant effect on individual control behavior of the millennial generation in West Java, while the variable of individual control behavior has a significant effect on decision making on sharia stock transactions for the PTMA millennial generation in the Java region West.